2013
DOI: 10.1155/2013/107954
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Stem Cells in the Development of Benign Prostate Hyperplasia and Prostate Cancer: Emerging Role and Concepts

Abstract: Benign Prostate hyperplasia (BPH) and prostate cancer (PCa) are the most common prostatic disorders affecting elderly men. Multiple factors including hormonal imbalance, disruption of cell proliferation, apoptosis, chronic inflammation, and aging are thought to be responsible for the pathophysiology of these diseases. Both BPH and PCa are considered to be arisen from aberrant proliferation of prostate stem cells. Recent studies on BPH and PCa have provided significant evidence for the origin of these diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 112 publications
0
24
0
3
Order By: Relevance
“…Understanding of the prostate stem cell biology is essential since there is a growing body of evidence suggesting that benign prostate hyperplasia and prostate cancer may arise from the stem or stem-like cell compartments [30]. In this study, we took advantage of the s-SHIP promoter-driven reporter to detect and isolate s-SHIP-expressing human prostate cells.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding of the prostate stem cell biology is essential since there is a growing body of evidence suggesting that benign prostate hyperplasia and prostate cancer may arise from the stem or stem-like cell compartments [30]. In this study, we took advantage of the s-SHIP promoter-driven reporter to detect and isolate s-SHIP-expressing human prostate cells.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between tissue development and adult tissue regeneration suggested a critical role of pluripotent cells in inflammation-induced tissue repair. Pluripotent prostate epithelial progenitor cells have been identified in normal prostate, BPH, and prostate cancer tissues (25,33). They were capable of regenerating other prostate cells, such as basal cell and luminal cells, in vitro or in vivo (19,21,24).…”
mentioning
confidence: 99%
“…It is characterized by hyperplasia of epithelial and stromal cells in the transition zone of the prostate gland, which can be observed histopathologically [24]. Stem cells in the human prostate have been identified and isolated using the cell surface markers such as CD44 [25], integrin α2β1 [26], CD133 (Prominin-1) [27] which, are believed to be responsible for the development and progression of proliferative disorders of the prostate such as prostate cancer and benign prostate hyperplasia [9,[28][29][30]. Based on high expression of α2β1 integrin, Collins and colleagues identified PSCs in the basal layer and showed that the α2β1 high integrin cells represent ~1% of basal cell population in the human prostate [26].…”
Section: Discussionmentioning
confidence: 99%